Ab Initio Investigation of Helium Mobility in La2Zr2O7 Pyrochlore - Yanxia Lu; Qing Peng; Chenguang Liu (Crystals, 2021)
The α-decay of incorporated actinides continuously produces helium, resulting in helium accumulation and causing security concerns for nuclear waste forms. The helium mobility is a key issue affecting the accumulation and kinetics of helium. The energy barriers and migration pathways of helium in a potential high-level nuclear waste forms, La2Zr2O7 pyrochlore, have been investigated in this work using the climbing image nudged elastic band method with density functional theory. The minimum energy pathway for helium to migrate in La2Zr2O7 is identified as via La–La interstitial sites with a barrier of 0.46 eV. This work may offer a theoretical foundation for further prospective studies of nuclear waste forms.